เศรษฐศาสตร์การเมืองของวิทยุกระจายระบบเอฟ.เอ็ม.ในกรุงเทพมหานคร - น้ำมนต์ พรหมเปี่ยม (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The objectives of the research are to study economic performance and market structure of Bangkok F.M. radio broadcasting during 1987-1996. Also this research will consider trend of concentration happening in the industry by applying the concentration ratio as an analytical framework. The research finds that, in terms of ownership form, all Bangkok F.M. radio stations have been owned by state agencies since the beginning. Although private companies are allowed to participate in broadcasting by renting airtime or seeking consession in some stations, the government still has the ownership of the stations untill present. Thailand s economic boom and the access to the concession by private companies in some radio stations in 1991 are main factors led to fierce competition among major program-producing companies in the industry. This causes the concentration and monopoly by a few media business groups such as Media Plus, A-Time Media, U&I Corporation, Pacific Corporation, and Broadcasting Network Thailand (BNT).